Олександра Псьол як читачка Шевченка - Харчук, Р. (Слово і Час, 2018)
Авторка статті з'ясовує, які вірші передавала Олександра Псьол на заслання Шевченкові.
На її думку, О. Псьол почала писати свої вірші саме під впливом Шевченка, у її випадку поет
був справжнім Пігмаліоном. The author of the paper finds out which poems Oleksandra Psiol sent to exiled Shevchenko. In the
researcher’s opinion, Oleksandra Psiol began to write her poems just under the infl uence of Shevchenko,
in her case Shevchenko was a real Pygmalion. Oleksandra Psiol is an important person not only in the
context of Shevchenko’s biography, but also in Ukrainian literature, because she was in fact the first
Ukrainian poetess not only of the romanticism period, but also of the time when Ukrainian literature was
taking its separate place in the literary stream of the Russian empire. Shevchenko’s infl uence on her poetics
was significant, but the poet himself did not consider her as an epigone, he saw a literary sister in her. Автор статьи выясняет, какие стихи передавала
Александра Псел в ссылку Шевченко.
По ее мнению, Александра Псел начала
писать свои стихи именно под влиянием Шевченко,
в ее случае поэт был настояним Пигмалионом.